Cerebral Palsy : Review of 49 Patients - Gulhis Deda; Ugur Karagol; Yavuz Gurer (Paediatrica Indonesiana, 1992)
Fourty nine cerebral palsied patients admitted between 1989-1990 are reviewed according to type of paresis and the incidence of epilepsy and mental retardation. Eighteen (36,7%) of these patients were epileptic and 22 (44.89%) were mentally retarded. Out of 6 right-sided hemiparetic patients 3 (50%) had clinical seizures being all generalized tonicclonic epilepsy. In the left-sided hemiparetic group only 1 patient (16,66%) had clinical seizures being left-sided focal epilepsy.